Compliment Response Strategies of English Pre-Service Teachers - Masita, Ella; Fortunasari; Hidayat, Marzul; Marzulina, Lenny; Kamil, Dairabi (Universitas Jambi, Indonesia, 2025)
Learning English goes beyond merely memorizing English words and grammar rules. Instead, understanding the socio-cultural background is essential as an important part of successful communication. As a part of politeness strategies, responding appropriately to an English compliment is an urgent skill to master especially by English teachers as they play an important rule for their students in the process of English learning. This article therefore is aimed at investigating how English pre-service teachers at Jambi University respond English compliments. The design of this study is descriptive qualitative. The data collection tool is an interview which then be analyzed using Thematic Analysis. Based on the data, three major findings have emerged, they are: the variations of students’ responses toward English compliments, the influences of Indonesian language system in students’ responses and students’ lack of ability in producing appropriate compliment responses.